Drug shortage management in Alabama hospital pharmacies - Oliver W. Holmes, III; Peter J. Hughes (University of Minnesota Libraries Publishing, 2013)
Purpose: The purpose of this study is to identify effective strategies used by Alabama hospitals to manage drug shortages. Moreover, this study aims to determine if there are any relationships among hospital size, utilization of a standard policy for drug shortage management and perceived usefulness of standard procedures for drug shortages. Methods: A paper survey was mailed to 129 hospital pharmacies in Alabama (per the Alabama Hospital Association directory). The survey consisted of 5 demographic questions, questions involving perception of current medication shortages, sources of information about shorted drugs, and frequency of discussion at P&T committee meetings. Most importantly, the survey contained questions about the use of a standard policy for handling drug shortages, the effectiveness of the policy if one is used, and an open-ended question asking the recipient to describe the policy being used. Results: A response rate of 55% was achieved as 71 surveys were completed and returned. Approximately 70% of the survey respondents described the current drug shortage issue as a top priority in their pharmacy department. The pharmacy distributor served as the primary source of information regarding drug shortages for 45% of the facilities. There is a direct relationship between size of hospital and likelihood of utilization of a standard policy or procedure for drug shortage management among the sample. The smaller facilities of the sample perceived their management strategies as effective more frequently than the larger hospitals. Conclusion: Common components of effective management strategies included extensive communication of shortage details and the ability to locate alternative products. The use of portable technology (e.g., Smart phones and tablets) along with mobile applications may emerge as popular means for communicating drug product shortage news and updates within a facility or healthcare system.   Type: Original Research